2014
DOI: 10.1556/eujmi-d-14-00014
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the GenoType MTBDRplus assay for rifampin and isoniazid resistance detection on sputum samples in Cote d'Ivoire

Abstract: We conducted an evaluation study on the GenoType MTBDRplus assay's ability to detect mutations conferring resistance to rifampin and isoniazid directly from sputum taken from 120 smear positive pulmonary patients from tuberculosis (TB) centers in Cote d'Ivoire.The sputum was decontaminated by N-acetyl-l-cysteine (NALC) and comparatively analyzed with the MTBDRplus assay version 2.0 and the mycobacterial growth indicator tube (MGIT) 960 automated drug susceptibility testing (MGIT-DST). The GeneXpert Mycobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(25 reference statements)
2
7
3
Order By: Relevance
“…INH sensitivity and specificity among AFB smear negative specimens in this study was 81.6% (95%CI 65.1–91.7) and 98.1% (95%CI 88.6–99.9) respectively, compared to 93.5% and 82.3% reported by Crudu et al N’guessan et al reported RIF sensitivity and specificity only among AFB smear positive specimens, and the only evident difference in assay performance was the sensitivity of RIF resistance (73.2%), which was significantly lower than reported in the current study (97.1%, 95%CI 94.9–98.4). 9 The sensitivity and specificity of MTBDR plus v2, as reported by Barnard et al, were 100% for both RIF and INH resistance, higher than both estimates from the current study. 8 …”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…INH sensitivity and specificity among AFB smear negative specimens in this study was 81.6% (95%CI 65.1–91.7) and 98.1% (95%CI 88.6–99.9) respectively, compared to 93.5% and 82.3% reported by Crudu et al N’guessan et al reported RIF sensitivity and specificity only among AFB smear positive specimens, and the only evident difference in assay performance was the sensitivity of RIF resistance (73.2%), which was significantly lower than reported in the current study (97.1%, 95%CI 94.9–98.4). 9 The sensitivity and specificity of MTBDR plus v2, as reported by Barnard et al, were 100% for both RIF and INH resistance, higher than both estimates from the current study. 8 …”
Section: Discussioncontrasting
confidence: 56%
“…Several small-scale studies have assessed the performance of this new assay version among homogenous populations, but a large-scale study in a diverse population has yet to be performed. 79 Additionally, the impact of AFB smear status, HIV status, body mass index (BMI), and other clinical factors associated with disease progression on the performance of MTBDR plus v2 have yet to be assessed. 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of datasets were cross-sectional in design and almost all were performed in either a regional or national reference laboratory setting. 48 datasets evaluated LPA for direct testing on sputum specimens [ 15 , 17 , 24 , 25 , 27 , 29 32 , 35 39 , 41 43 , 46 , 47 , 49 , 50 , 52 , 57 , 59 , 62 69 , 71 , 72 , 74 , 77 – 82 , 84 , 87 , 91 , 93 ] and 46 datasets evaluated LPA for indirect testing on culture isolates [ 17 , 23 , 25 28 , 33 – 35 , 37 , 39 , 40 , 44 , 45 , 48 , 51 58 , 60 – 62 , 68 , 70 , 72 , 73 , 75 , 76 , 78 , 79 , 83 , 85 , 86 , 88 90 , 92 , 94 ]. 83 datasets evaluated Hain V1, five datasets evaluated Hain V2 [ 15 , 30 , 36 , 72 ] and six datasets evaluated Nipro [ 17 , 72 , …”
Section: Resultsmentioning
confidence: 99%
“…57 datasets included data on the diagnostic accuracy of LPA for MDR-TB detection, with a total of 13 033 samples that included 4248 (33%) confirmed MDR-TB cases [ 23 – 29 , 32 , 34 , 35 , 37 , 38 , 41 44 , 48 , 50 , 52 56 , 58 64 , 66 69 , 71 73 , 75 , 78 , 80 , 82 , 84 , 88 , 90 , 91 , 93 ]. Bivariate meta-analysis of these datasets revealed a pooled sensitivity of 92.9% (95% CI 90.4–94.8%) and specificity of 99.3% (95% CI 98.7–99.6%) ( table 3 and figure 3c ).…”
Section: Resultsmentioning
confidence: 99%
“…For the GenoType MTBDRplus assay, previous studies have reported the sensitivity, specificity, PPV and NPV values in detecting INH resistance as ranging between 60%-100%, 95.1%-100%, 97.4%-100% and 90.7%-100%, respectively. In addition, this assay's sensitivity, specificity, PPV and NPV values in detecting RIF resistance are in the range of 82.3%-100%, 73.2%-100%, 81%-100% and 98.9%-100%, respectively [16][17][18][19][20][21][22][23][24][25]. When the results were evaluated, this assay seemed to be more sensitive for detecting RIF resistance than INH resistance.…”
Section: Resultsmentioning
confidence: 95%